Thinking about Judges and Judicial Performance: Perspective of the Public and Court Users - David Rottman; Tom Tyler (Oñati Socio-Legal Series)
Studies of the courts, conducted primarily in the United States, suggest that the way legal professionals think about judging underpins nearly all official evaluations of judicial performance. The general public has a different view than lawyers of judging that merits consideration along with the type of criteria emphasized by the legal community. Research demonstrates that the public places the greatest importance on the extent to which a judge reaches decisions through a process that meets the public's expectations of fairness. Surveys of California residents and California attorneys are used to demonstrate the importance of procedural justice for explaining whether people have trust in the courts and regard court decisions as legitimate. The article describes and critiques existing judicial performance evaluation programs that incorporate procedural justice principles as a dimension for measuring judicial quality through both survey and observational methods.